Cognitive and Behavioral Development of 9-Year-Old Children After Maternal Cancer During Pregnancy: A Prospective Multicenter Cohort Study - Van Assche, Indra A; Huis In 't Veld, Evangeline A; Van Calsteren, Kristel; van Gerwen, Mathilde; Blommaert, Jeroen; Cardonick, Elyce; Halaska, Michael J; Fruscio, Robert; Fumagalli, Monica; Lemiere, Jurgen; van Dijk-Lokkart, Elisabeth M; Fontana, Camilla; et al. (Journal of clinical oncology, 2023)
Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported.This multicenter cohort study reports on the long-term effects of prenatal exposure to maternal cancer and its treatment on cognitive and behavioral outcomes in 9-year-old children. In total, 151 children (mean age, 9.3 years; range, 7.8-10.6 years) were assessed using a neurocognitive test battery and parent-report behavioral questionnaires. During pregnancy, 109 children (72.2%) were exposed to chemotherapy (only or in combination with other treatment modalities), 18 (11.9%) to surgery only, 16 (10.6%) to radiotherapy, one to trastuzumab, and 16 (10.6%) were not exposed to oncologic treatment. Mean cognitive and behavioral outcomes were within normal ranges. Gestational age at birth showed a positive association with Full Scale Intelligence Quotient (FSIQ), with the average FSIQ score increasing by 1.6 points for each week increase in gestational age (95% CI, 0.7 to 2.5; P < .001). No difference in FSIQ was found between treatment types (F[4,140] = 0.45, P = .776). In children prenatally exposed to chemotherapy, no associations were found between FSIQ and chemotherapeutic agent, exposure level, or timing during pregnancy. These results indicate a reassuring follow-up during the critical maturational period of late childhood, when complex functions develop and rely on the integrity of early brain development. However, associations were observed with preterm birth, maternal death, and maternal education.
Keywords: Prenatal Exposure Delayed Effects; kohortové studie; Neoplasms; zpožděný efekt prenatální expozice; Cohort Studies; Child; předčasný porod; Pregnancy; těhotenství; dítě; Prospective Studies; Premature Birth; novorozenec; kognice; lidé; ženské pohlaví; Humans; Infant, Newborn; nádory; Female; Cognition; prospektivní studie